Analysis of Mangrove Vulnerability Level using Remote Sensing Data in Comal Estuary, Pemalang - Sanjoto, Tjaturahono Budi; Husna, Vina Nurul; Aji, Ananto (Universitas Negeri Medan, 2025)
Human activity around mangrove areas can harm their health, despite their economic benefits to local communities. A study of the Comal estuary found that increased human activity was not matched by efforts to protect the mangroves. This lack of awareness is likely due to a lack of information about the importance of mangroves and their vulnerability. The study used Sentinel-2A and field measurements to assess vulnerability based on factors like mangrove density, salinity, and distance from the shore. That factor were used to generate vulnerability value based on weighted overlay analysis (vulnerability index). The results showed that the eastern part of the estuary was highly vulnerable to wave damage (abrasion) due to its location. In contrast, the central part of the estuary had low vulnerability due to its denser and healthier mangroves. These findings were confirmed by field observations: areas with low vulnerability had dense, healthy mangroves, while areas with high vulnerability had damaged and broken trees. The existence of the vurnerability class can be used as a recommendation for further mangrove management. Restoration can be applied in areas of high mangrove vulnerability. The area has a very low mangrove density due to the large number of mangroves damaged by abrasion, so replanting mangroves in the area is highly recommended. Mangrove planting also needs to require great attention, especially in the area has a problem in the form of large ocean waves, so the construction of a breakwater with a “Shark Tooth” formation is recommended